Pengaruh Metode Cantol Raudhoh Terhadap Kemampuan Pengenalan Membaca Pada Anak Kelompok B Di TK Mojorejo 4 Karangmalang Sragen Tahun Ajaran 2016/2017 - Ratna Sari, Desti, Sri Slamet, M.Hum., M.Pd (2017)
The purpose of the research is to determine the effect of Cantol Raudhoh Methods to the Reading Recognition Capabilities for the children in group B at TK Mojorejo 4 Karangmalang Sragen in the academic year of 2016/2017. The method of the research used quantitative method. It was pre-experimental research using one group pretest-posttest design. This research was conducted in February 2017 at TK Mojorejo 4 Karangmalang Sragen. The subject of the research were the children in group B in TK Mojorejo 4 Karangmalang Sragen with the total amount of 17 children. The data analysis techniques of the research used ttest with SPSS 16.0 for windows. The results of data analysis using ttest was obtained tcount-16.483 ≤ ttable-1.7459 so H0 rejected and Ha accepted. It means that there is the influence of Cantol Raudhoh Methods foward the Reading Recognition Capabilities for the Children in group B at TK Mojorejo 4 Karangmalang Sragen in the Academic year of 2016/2017. Keywords: Cantol Raudhoh Methods, Reading Recognition Capabilities